Experimental, Ab İnitio And Density Functional Theory Studies On Sulfadiazine - Özel, Ayşen E.; AKYÜZ, SEVİM; ILDIZ, GÜLCE ÖĞRÜÇ (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2009)
In the present study, combined experimental and computational study on molecular vibrations of free sulfadiazine has been reported. The theoretically possible stable conformers of free sulfadiazine molecule in electronically ground state were searched by means of torsion potential energy surfaces scan studies through C1-C7-S8-N9, C7-S8-N9-C10 and S8-N9-C10-N11 dihedral angles, at both semi-empirical PM3 and B3LYP/3-21G levels of theory. The final geometrical parameters for the obtained stable conformers were determined by means of geometry optimization carried out at ab initio HF/6-31G++(d,p) and DFT/B3LYP/6-31G++(d,p) theory levels. The harmonic and anharmonic vibrational wavenumbers and IR intensities were calculated at the same theory levels used in geometry optimization. The modes of the fundamental vibrations were characterized depending on their the total energy distribution (TED%). In order to fit the calculated harmonic wavenumbers to experimental ones, dual scale factors were used. The experimental infrared and Raman spectra of sulfadiazine in solid phase have been measured and compared with the calculated vibrational spectra of each conformer. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ab initio HF; density functional theory; DFT; infrared and raman spectroscopy; sulfadiazine; molecules; complexes; spectra; yoğunluk fonksiyonu teorisi; infrared ve raman spektroskopisi; moleküller; kompleksler; spektrumlar